Aggregating ability of ferric chloride in the presence of phosphate ligand. (1st November 2019) - Lartiges, B.; El Samrani, A.G.; Montargès-Pelletier, E.; Bihannic, I.; Briois, V.; Michot, L.
Abstract: Complexing anions such as phosphate or silicate play an ambivalent role in the performance of hydrolyzing metal coagulants: On one hand, they significantly interfere with the hydrolytic pathway of conventional iron or aluminum coagulants, the associated destabilization mechanism remaining rather elusive; on the other hand, they have been shown to be key ingredients in the formulation of innovative coagulant solutions exhibiting improved removal efficiency, their action mechanism at the molecular scale being presently poorly understood. In this paper, we explore the effect of small additions of phosphate ligand on the chemical coagulation of silica nanoparticles with ferric chloride. Transmission Electron Microscopy-Energy Dispersed X-ray Spectroscopy (TEM-EDXS) combined with Extended X-ray absorption Fine Structure Spectroscopy (EXAFS) at the Fe K-edge are used to provide an insight into the nature of coagulant species, whereas jar-tests, laser diffraction, Small Angle X-ray Scattering (SAXS), and electrophoretic mobility, are used to investigate the aggregation dynamics of silica particles in the presence of phosphate ligand. We show that, in spite of a slight increase in the consumption of iron coagulant, the addition of phosphate significantly improves the formation of silica aggregates provided that the elemental Fe/P ratio remains above 7. Such effects originate from both a large increase in the overall number of coagulant species, the binding of a phosphate ligand terminating the growth of polymeric chains of edge-sharing Fe octahedra, and a change in the nature of the coagulant species that evolves with the Fe/P ratio, small polycations built-up from Fe-oligomers linked by phosphate tetrahedra being eventually formed. Those non-equilibrium nanosize Fe–P coagulant species assemble the silica nanoparticles to form hetero-aggregates whose structure is consistent with a Diffusion-Limited Cluster Aggregation mechanism. Graphical abstract: Image 1 Highlights: The presence of phosphate complexing anions controls the nature of coagulant species. Phosphate ligands terminate the growth of edge-sharing Fe octahedra polymer chains. Optimal coagulant species are formed with a Fe/P elemental ratio around 7. Nanosize Fe–P coagulant species assemble the particles to form hetero-aggregates. The structure of aggregates is governed by a Diffusion Limited Cluster Aggregation.